Preliminary results from antarctic albedo from remote sensing observations - G. Traversa; D. Fugazza; A. Senese; G. A. Diolaiuti (Comitato glaciologico italiano, 2019)
The aim of the study is to analyse the surface albedo of the Ant-arctica and investigate eventual signals of variations in space and time between summer 2000/2001 and 2011/2012 by means of the GLASS albedo product. We followed a step-by-step procedure from micro- to macro-scale. At first, we analysed 95 glaciers around the continent, and we found limited temporal variability. Then, looking at spatial varia-tions, we divided Antarctica based on oceanic basins and by continen-tality. We found spatial signals, since mean albedo values range between 0.79 (Pacific and Atlantic basins) and 0.82 (Indian basin) and between 0.76 (along the shore) and 0.81 (inner continent). An increasing vari-ability was found from the inner continent to the shore, and heteroge-neous patterns among the basins, most likely due to meteorological and environmental conditions (mainly: temperature, precipitation, katabatic winds). Finally, the general patterns observed (considering the specific gla-ciers, the three basins and the three continentality sectors) were verified by the analysis of the whole continent and we did not find a significant change of summer averages over time, as they range between 0.79 and 0.80.